Dosage Problems in Children: Well-Known Facts and Unresolved Issues - Olga A. Mikhailova; Vladimir N. Drozdov; Natalia В. Lazareva; Evgeniya V. Shikh (Вопросы современной педиатрии)
The problem of dosing drugs at an early age is conditioned by specific metabolism of medicinal products (MP) in the child's body. Currently, there are a few clinical trials on the study of physiological characteristics in different periods of childhood and systematised data. It is still relevant to understand the characteristic differences that affect the bioavailability, distribution and excretion of MP, especially in children over one month of life. The results of such studies are necessary in order to formulate the recommendations for use of MP in children taking into account their age and compensate for the lack of data from direct clinical trials in pediatrics. The possibility of using a dose calculation method regarding the fat content of the body in different periods of childhood and the chemical properties of the substance has been discussed.